Biaya dan Outcome Hemodialisis di Rumah Sakit Kelas B dan C - Tania, Firda; Thabrany, Hasbullah (Jurnal Ekonomi Kesehatan Indonesia, 2016)
Chronic Kidney Disease (CKD) is a condition that is increasing in incidence in Indonesia, consuming a lot of National Health Insurance (JKN) public funds. In the JKN program, hemodialysis (HD) for treating CKD is guaranteed but requires a balance between costs and outcomes. Since 2014, BPJS has covered almost all HD costs in Indonesia with different Casemix Base Group (CBG) rates according to hospital class.